An engineering method for simulating dynamic interaction of moored ship with first-year ice ridge. (1st January 2019) - Zhou, Li; Gao, Junliang; Li, Dongqin
Abstract: This paper aims to present a new tool to simulate dynamic ice ridge-structure interaction in 6 Dofs in time domain. The global forces caused by ice ridge as well as responses of the structure are simulated. The ice ridge loads are composed of loads due to sail, consolidated layer and unconsolidated keel. The sail load is neglected since it is small compared to the other two components. The consolidated layer could be taken as level ice. The related level ice force is simulated by integrating ice breaking force and ice accumulation force. Two ice failure modes, namely bending and crushing, are used when calculating the breaking force. A numerical model is used to calculating the ice accumulation force underwater by determining the relative horizontal positions and motions of ice rubble to the strip of the structure. The ice load due to the unconsolidated keel is calculated based on a modified theoretical model in probabilistic design. The motions of the moored ship are also applied to update the waterline of the hull at each time step to estimate precisely local contact areas between ice and hull. The simulation results are compared with model test data. Highlights: We propose a new method to simulate dynamic interaction between ice ridge and ship. Both bending and crushing failures are considered when calculating ice breaking force for consolidated layer. The method to consider the motions of the ice rubble and the resulting forces are proposed. The action from unconsolidated keel is also included by using an appropriate mathematical model. The ship motion is obtained by solving equation of motion in 6 Dofs and used to update waterline.